Risk of developmental dysplasia of the hip in breech presentation: the effect of successful external cephalic version. Issue 5 (12th November 2012) - Lambeek, AF; De Hundt, M; Vlemmix, F; Akerboom, BMC; Bais, JMJ; Papatsonis, DNM; Mol, BWJ; Kok, M
<x xml:space="preserve">Abstract</x> Please cite this paper as: Lambeek A, De Hundt M, Vlemmix F, Akerboom B, Bais J, Papatsonis D, Mol B, Kok M. Risk of developmental dysplasia of the hip in breech presentation: the effect of successful external cephalic version. BJOG 2012; DOI: 10.1111/1471‐0528.12013. Objective To evaluate the effect of successful external cephalic version on the incidence of developmental dysplasia of the hip (DDH) requiring treatment in singleton breech presentation at term. Design Observational cohort study. Setting Three large teaching hospitals in the Netherlands. Population Women with a singleton breech presentation of 34 weeks of gestation or more, who underwent an external cephalic version attempt. Methods We made a comparison of the incidence of DDH between children born in breech presentation and children born in cephalic presentation after a successful external cephalic version. Main outcome measure The incidence of DDH requiring either conservative treatment, with a harness, or surgical treatment. Results A total of 498 newborns were included in the study, of which 40 (8%) were diagnosed with DDH and 35 required treatment. Multivariate analysis showed that female gender (OR 2.79, 95% CI 1.23–6.35) and successful external cephalic version (OR 0.29, 95% CI 0.09–0.95) were independently associated with DDH. Conclusions A successful external cephalic version is associated with a lower incidence of DDH, although a high percentage of children born after a successful external cephalic version still appear to have DDH. A larger cohort study is needed to establish the definite nature of this relationship. Until then, we recommend the same screening policy for infants born in cephalic position after a successful external cephalic version as for infants born in breech position.